2017
DOI: 10.1257/aer.20160055
|View full text |Cite
|
Sign up to set email alerts
|

Multi-Category Competition and Market Power: A Model of Supermarket Pricing

Abstract: In many competitive settings consumers buy multiple product categories, and some prefer to use a single firm, generating complementary cross-category price effects. To study pricing in supermarkets, an organizational form where these effects are internalized, we develop a multi-category multi-seller demand model and estimate it using UK consumer data. This class of model is used widely in theoretical analysis of retail pricing. We quantify crosscategory pricing effects and find that internalizing them substant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
71
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 130 publications
(86 citation statements)
references
References 49 publications
2
71
0
1
Order By: Relevance
“…In particular, we transform the consumer's original non-differentiable maximization problem into a list of problems that are differentiable and have explicit solutions. This is similar to the method in Thomassen et al [2017]. After doing so, we then simulate each consumer's optimal plan choice and usage decision, given a set of model parameters.…”
Section: Model Estimation Methods and Identification Iii(i) Estimentioning
confidence: 99%
See 2 more Smart Citations
“…In particular, we transform the consumer's original non-differentiable maximization problem into a list of problems that are differentiable and have explicit solutions. This is similar to the method in Thomassen et al [2017]. After doing so, we then simulate each consumer's optimal plan choice and usage decision, given a set of model parameters.…”
Section: Model Estimation Methods and Identification Iii(i) Estimentioning
confidence: 99%
“…15 Our approach to solving the usage decision problem is similar to the method in Thomassen et al [2017] except that we have four scenarios for each service leading to 4 K combinations, compared with 2 K in their paper, where K is the number of products.…”
Section: Model Estimation Methods and Identification Iii(i) Estimentioning
confidence: 99%
See 1 more Smart Citation
“…10 The median number of stores within 10 miles of given tract is 41. In their analysis of the UK grocery market, Thomassen et al (2017) assume that the choice set is the nearest 30 stores, noting that the fraction of expenditures outside that set is only 1.2%. 11 In our setting, the presence of the logit shock could add an element of misspecification if D is set too large, because all outlets in the choice set will attract at least some consumers.…”
Section: Modelmentioning
confidence: 99%
“…1 A primary motivation for pursuing this alternative source of variation is the challenge of obtaining price data for all outlets. However, the widespread practice of uniform grocery pricing (e.g., Thomassen et al, 2017) suggests that price effects may not be well identified from cross-sectional variation alone, even if prices were observed. In this sense, our approach complements Conlon and Mortimer (2013), who use variation in the availability of products in lieu of price changes to measure diversion 2 Holmes' analysis of Wal-Mart abstracted from competition to focus on how the dynamics of Wal-Mart's expansion decisions were influenced by the scale economies associated with operating a dense network of stores.…”
mentioning
confidence: 99%